Embracing the provinces - Driel-Murray, Carol van; Ivleva, Tatʹi︠a︡na; Ivleva, Tatʹi︠a︡na; Bruin, Jasper; Bruin, Jasper; Driessen, Mark; Driessen, Mark (Oxbow Books, 2018)
"This is a collection of essays focused on people and their daily lives living in the Roman provinces, c. 27 BC-AD 476. The main aim is to showcase the vibrancy of Roman provincial studies and suggest new directions, or new emphasis, for future investigation of the Roman provincial world. It capitalizes on a wealth of data made available in recent decades to provide a holistic view on life in the Roman provinces by analysing various aspects of daily routine in the frontier regions, such as eating, dressing, and interacting. The contributors, who are acknowledged experts in their fields, make use of innovative interpretations and modern approaches to address current issues in the study of the provinces and frontiers of the Roman Empire. Twenty-one essays are cohesively structured around five themes, encompassing studies on the female and juvenile presence on Roman military sites, Roman provincial cooking, and Roman cavalry and horse equipment. For the first time in the Roman provincial scholarship the volume has a special section on the subject of Roman leather, providing a much-needed overview of the current stance of work. A few papers deal also with experimental archaeology. The essays reflect a wide geographical and chronological range, while retaining thematic consistency"--